Study of Oxidative–Reductive Potential Changes in the Enrichment of Oxidized Polymetallic Ores - Alima Mambetaliyeva; Tansholpan Tussupbekova; Leyla Sabirova; Guldana Makasheva; Kanay Rysbekov; Madina Barmenshinova (Applied Sciences)
This paper presents an analysis of the current state of processing lead–zinc ores from the Koskudyk deposit (Kazakhstan). At present, polymetallic ores are being extracted from the Ridder-Sokolnoye, Zyryanovskoye, Maleevskoye, and Achisai deposits. However, the reserves of rich and easily beneficiable ores are being depleted, and the supply of raw materials from the developed deposits does not exceed 25 years. As a result, more complex and difficult-to-enrich oxidized and mixed ores are being involved in production, and the extraction of non-ferrous metals from these ores presents a significant technological challenge. The most effective method for enriching oxidized polymetallic ores is flotation with preliminary sulfidization. Laboratory studies were conducted on a sample of oxidized lead–zinc ore from the Koskudyk deposit, which contains 79.69% oxidized lead compounds and 84.72% oxidized zinc compounds. This study examines the effect of sulfidization using sodium sulfide and determines the oxidative–reductive potential (ORP) levels for various reagent dosages. The experiments demonstrated that a sodium sulfide dosage of 700 g/t at an ORP of −200 mV yields the most effective lead flotation, resulting in a lead recovery of 50.07%. Zinc recovery remained relatively unchanged across all tests, confirming the limited response of oxidized zinc minerals under the applied sulfidization conditions. The highest beneficiation efficiency was achieved within the ORP range of −160 to −200 mV, beyond which lead recovery began to decline. The findings underscore the importance of optimizing ORP to ensure the formation of a stable sulfide film on mineral surfaces and efficient collector attachment. These results provide practical guidance for improving flotation performance of oxidized ores and demonstrate the need for additional activation strategies in zinc recovery.